A study of the prevalence of obstructive sleep apnea among university students with excessive daytime sleepiness. - Campo-Arias, Adalberto; Pedrozo-Pupo, John Carlos; Cecilia Caballero-Domínguez, Carmen (Revista Facultad de Medicina de la Universidad Nacional de Colombia, 2025)
Introduction: Obstructive sleep apnea (OSA) is one of the leading secondary causes of sleepiness. However, the literature on its prevalence among health science students with sleepiness is scarce. Objective: To establish the prevalence of OSA among students with excessive daytime sleepiness (EDS) at a university in Santa Marta, Colombia. Materials and methods: A descriptive prevalence study was carried out in 655 health science students (medicine, nursing, dentistry, and psychology). The participants completed the Epworth Sleepiness Scale (ESS, Cronbach's alpha 0.82), as well as an ad hoc questionnaire (sociodemographic information and clinical variables related to OSA). Students with EDS (ESS=11) underwent home respiratory polygraphy to confirm the presence of OSA (apnea/hypopnea index [AHI] =5). Results: Of the 655 students screened, 186 (28.40%) had EDS. In this subgroup, the mean age was 21.08 years (SD=2.47) and 70.43% were female. Furthermore, 67.20% were medical students; 12.37% were nursing students; 10.75% were psychology students; and 9.68% were dentistry students. The mean AHI was 1.40 (SD=2.53) and 19 (10.21%) had OSA, of which 18 (94.74%) were mild cases (AHI=5.00-14.99). Conclusions: In the present study, carried out at a public university in Santa Marta, 10% of health sciences students with EDS were diagnosed with OSA. Further studies should investigate OSA independently of the EDS diagnosis as determined by the ESS score.